Analysis of the Role of Pantai Panjang Bengkulu Tourism Objects in Increasing Community Income from an Islamic Economic Perspective - Dharma Setiawan; Subandrio Subandrio; Amir Mukadar; Bambang Rahmanto (Penerbit Jurnal Indonesia, 2024)
The tourism sector is one of the people's economic potentials that needs to be developed in order to improve community welfare and regional development. Panjang Beach is one of the most famous tourist attractions in Bengkulu. One of the factors is that the Panjang Beach tourist attraction is able to open up employment opportunities for the local community by becoming auxiliary workers and opening micro, small and medium businesses run by the community around the area. So there is management and many regional development programs on the grounds that the Panjang Beach tourist attraction is able to produce economic benefits for the community. This research aims to analyze the role of the Bengkulu Panjang Beach tourist attraction in increasing people's income according to an Islamic economic perspective. The types of research used in this thesis are field research and library research . The methods used to collect data in this research are observation, documentation, interviews and questionnaires. The results of the research can be concluded that the role of the Bengkulu Panjang Beach tourist attraction is able to make a very big contribution as a place that is able to absorb labor as well as providing employment opportunities for the surrounding community in particular and based on data obtained both practically through observation and theory, it can be concluded it is said that the business activities that occur in the Panjang Beach tourist area of Bengkulu and those carried out by the community around the Panjang Beach tourist attraction are in accordance with the Ijarah principles. Keywords: Tourist Attractions, Long Beach, Income, Islamic Economy